The sculptor of time: some keys to Gilles Deleuze’s “cinematographic philosophy” - Ruiz Moscardó, Javier (Estudios de Filosofía, 2018)
Gilles Deleuze has offered in his two studies on cinema —L’image–mouvement et L’image– temps— one of the most ambitious proposals of the last decades on the relation between philosophy and cinema, constructing a true “cinematographic philosophy” and inaugurating, in parallel to Stanley Cavell, a fruitful line of philosophical research that has been called “film–philosophy”. His first work focuses, essentially, on a metaphysics of time inspired by the philosophy of Henri Bergson, but using the possibilities of cinema to complement and transcend the ideas of the author of L’évolution créatice. In his second work, on the other hand, Deleuze analyzes film modernity, together with the new regime of images that it promotes, as a symptom of contemporary nihilism and in turn as a tool that can collaborate in its overcoming. We will try to make a general presentation of the keys of the Deleuzian approach, taking as a reference the following two axes: the conception of cinema as a true ontological model capable of allowing us to think of the time and the universe in a promising way, and the aptitudes of cinema as an ethical instance from which to oppose the dangers of contemporary nihilism.